2014
DOI: 10.1002/jnm.2002
|View full text |Cite
|
Sign up to set email alerts
|

New study of the abnormal behavior of the low temperature dependence of the current in inhomogeneous Schottky diode

Abstract: In this study, we show clearly why unexpected observations have been reported in the current-voltage curves of Schottky diodes, containing barrier inhomogeneities generated by using the analytical results based on a Gaussian distribution model of barrier heights. The Chand's calculations have shown that the current (saturation current) at low temperatures may exceed the current (saturation current) at high temperatures when the effective barrier height is calculated from an appropriate integral with integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…and the temperature coefficient a f for Mo/4H-SiC diodes at various doses and different diameters. current at low temperatures when compared to the saturation current at high temperatures [22]. The BEEM studies have reported the low values of the standard deviation; 0.03, 0.04 [25], 0.02 [26], and 0.013-0.022 V [27] at room temperature and ∼0.011-0.021 V [24] in the temperature range of 129-252 K.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…and the temperature coefficient a f for Mo/4H-SiC diodes at various doses and different diameters. current at low temperatures when compared to the saturation current at high temperatures [22]. The BEEM studies have reported the low values of the standard deviation; 0.03, 0.04 [25], 0.02 [26], and 0.013-0.022 V [27] at room temperature and ∼0.011-0.021 V [24] in the temperature range of 129-252 K.…”
Section: Resultsmentioning
confidence: 96%
“…It presents the Werner's model for inhomogeneous Schottky diode. Most of the workers use this equation for extracting the inhomogeneous parameters f and s. However, when we apply this method the Schottky diodes exhibit higher currents at low temperatures than at high temperatures [15,22]. This observation is thus inconsistent with the thermionic emission-diffusion theory.…”
Section: Theory and Extraction Methods Of The Inhomogeneous Parametersmentioning
confidence: 96%
“…Chand and Bala [4] studied inhomogeneous diodes and observed the crossing of the I-V curves measured at low temperatures up to 100 K with I-V curves measured at higher temperatures. Latreche and Ouennoughi [5] carried out recently a similar study in which this effect has been confirmed, but the physical interpretation of the effect was rather different. Osvald and Horváth [6] simulated by the drift-diffusion approximation I-V curves of n-Si Schottky diodes with a p-type surface inversion layer in the temperature region 80-320 K. The intersection of the I-V curves appeared already in the linear section of the semi-logarithmic I-V curves.…”
Section: Introductionmentioning
confidence: 80%